2008
DOI: 10.1038/ng.218
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis susceptibility loci at chromosomes 10p15, 12q13 and 22q13

Abstract: The WTCCC study identified 49 single nucleotide polymorphisms (SNPs) putatively associated with RA at p=1×10 -4 -1×10 -5 (Tier 3). Here, we show that 3 of these SNPs, mapping to chromosome 10p15 (rs4750316), 12q13 (rs1678542) and 22q13 (rs3218253), are also associated (trend p = 4×10 -5 , p=4×10 -4 and p=4×10 -4 , respectively) in a validation study of 4,106 RA cases and an expanded reference group of 11,238 subjects, confirming them as true susceptibility loci in Caucasians.Rheumatoid arthritis (RA) is a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
109
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 12 publications
7
109
0
3
Order By: Relevance
“…29 The association of rs1678542/KIF5A variant with MS, uncovered for the first time in this work, was first associated with RA in European populations. 18,30 The rs1678542/KIF5A is located 194 kb apart from the rs703842/methyltransferase-like protein 1 3 0 UTR with a linkage disequilibrium r 2 of 0.184. The latter polymorphism is the most strongly associated SNP with MS in the locus in the GWAS carried out by the Australia and New Zealand Multiple Sclerosis Genetics Consortium.…”
Section: Kif5a Cd226 and Sh2b3 Variants Associate With Ms A Alcina Ementioning
confidence: 99%
“…29 The association of rs1678542/KIF5A variant with MS, uncovered for the first time in this work, was first associated with RA in European populations. 18,30 The rs1678542/KIF5A is located 194 kb apart from the rs703842/methyltransferase-like protein 1 3 0 UTR with a linkage disequilibrium r 2 of 0.184. The latter polymorphism is the most strongly associated SNP with MS in the locus in the GWAS carried out by the Australia and New Zealand Multiple Sclerosis Genetics Consortium.…”
Section: Kif5a Cd226 and Sh2b3 Variants Associate With Ms A Alcina Ementioning
confidence: 99%
“…A perfect proxy located at 60 kb from TNFRSF14 in 1p36 (rs3890745, r 2 ¼ 1) was found associated with rheumatoid arthritis by metaanalyses of two genome-wide studies; 6 the role of this gene in disease risk was also validated by a study of a strongly correlated variant (rs10910099, r 2 ¼ 0.96) in an independent cohort. 7 The TNFRSF14 gene is also known as herpes virus entry mediator (HVEM), and human herpes viruses have often been involved in the aetiology of multiple sclerosis (MS). 8 The entry of viruses into cells is a complex process, which is still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The region has provided some prime examples of evolving genetic research. Initially associated with T1D susceptibility using a candidate gene and tag SNP approach [15], further studies revealed association to other autoimmune diseases, including MS [16] and rheumatoid arthritis [17], and demonstrated that multiple genetic markers were needed to explain the T1D association [18]. Genotype to phenotype studies have demonstrated that disease-associated variants in the region also associate with IL2RA mRNA expression and CD25 protein expression on the surface of naive and memory CD4 + T cells [19][20][21] and sensitivity of memory CD4 + T and activated T regulatory cells to IL-2 [22].…”
Section: Introductionmentioning
confidence: 99%